APLIKASI PERSEDIAAN BAHAN BANGUNAN BERBASIS WEB PADA TOKO TB AGENG JAYA CILOPADANG - Riswanto, Beny; Mutingudin (Jurnal Teknologi dan Bisnis, 2020)
Data processing in a building store is generally the system used is still manual, so usually transaction data or sales reports are not neat because there are so many transaction documents that may be tucked away or lost. The Web-Based Building Material Inventory Application at the TB Ageng Jaya Store is expected to help make it easier, especially in inventory (stock). The background of the TB Ageng Jaya Store, which initially only sold paint and ceramics, developed into a building shop that was more complete than before and made manual data or reports programmed. The research method of this thesis is to provide transaction convenience services to consumers and provide good reports to building shop owners and in this research method using literature methods, interview methods, observation methods and design and build methods. The conclusion of this thesis is to process building store data from manual to programmed which is supported by the PHP programming language and MYSQL Server database and Adobe Dreamweaver CS6 Web editor. The results achieved with the Web-Based Building Materials Inventory Application at the TB Ageng Jaya Store, the TB Ageng Jaya shop owner can carry out data processing so that it makes his task easier in terms of data processing and can also make services to customers more efficient. For further research, it is hoped that this program will be able to improve so that it can have a wider reach.